Experimental Study of the Change in the Mass of Water Droplets in their Motion Through High-Temperature Combustion Products; Journal of Engineering Physics and Thermophysics; Vol. 86, iss. 6 - Volkov R. S. Roman Sergeevich; Vysokomornaya O. V. Olga Valeryevna; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2013, 2013)
Title screen